The Analysis of Israel – Turkey engagement on Syria and the US Foreign Policy of pulling out forces: Who controls what? - Kristian Montolalu, Reynaldo Rudy (Jurnal Diplomasi Pertahanan, 2021)
The issue of Syrian Civil war has tinted the International Relations issue at least from 2011 where a protest against President Assad’s regime resulted to the large-scale war between the anti-government rebel group which get backed by the United States, Turkey, Saudi Arabia and their other supported ally in the region while the Syrian government has the back up from Russia and Iran. There are three campaigns that influence the full-scale of conflict; the effort against Islamic State, tension between the Syrian government and the opposition as well as related to Turkish forces military operations against Syrian Kurds. The US foreign policy to give sanctioned to Syrian government up to its decision of pulling out forces in President Donald Trump administration has contemplated the bloody drama in Syria. These phenomena are then created a new era of conflict between Israel and Turkey which some says, actually share the same strategy.